Development and Evaluation of the CASTLE Trial Online Sleep Intervention for Parents of Children with Epilepsy - Wiggs, Luci; Cook, Georgia; Hiscock, Harriet; Pal, Deb K.; Gringras, Paul (Frontiers in Psychology, 2021)
Introduction: Many of the sleep problems experienced by children with epilepsy (CWE) have the same behavioural basis as common sleep problems seen in typically developing (TD) children. Behavioural sleep interventions are widely used to treat these sleep problems in TD children and are hypothesised to be effective for CWE. However, specific considerations need to be addressed and incorporated into a behavioural sleep intervention (BSI) for CWE to ensure the intervention is tailored to this population’s needs. This paper details developing and tailoring an online BSI for parents of CWE, to be used in the CASTLE (Changing Agendas on Sleep, Treatment and Learning in Epilepsy) Sleep-E clinical trial. Method: In phase one, two existing theory-driven pediatric BSIs were adapted into an online behavioural sleep intervention (CASTLE Online Sleep Intervention or COSI) which specifically incorporated the needs and requirements reported by nine parents of CWE. Scoping their needs included conducting interviews with three CWE so that they could contribute to the overall intervention content. In phase two, six parents participated in a feasibility study, reviewing and feeding back on COSI until parental approval was achieved. Results: In phase one, a range of adaptations was made to the content and presentation of intervention material to acknowledge and emphasise the key seizure-specific issues to ensure COSI best met parents’ of CWE needs. Adaptations included embedding parent and child experiences in the intervention, including particular information requested by parents, such as the links between sleep and seizures and managing child and parental anxieties around sleep, as well as developing functionality to personalise the delivery of content. In phase two, parents confirmed that they found the final version of COSI to be functional and appropriate (after one round of review) for use by parents of CWE and that 100% would recommend it to other families who have CWE. Discussion: It is hoped that the use of evidence-based BSIs, adapted to consider salient epilepsy-specific factors, will increase parent-engagement, COSI’s relevance for this particular patient group and overall efficacy in improving sleep in CWE. The effectiveness of COSI will be tested in the CASTLE Sleep-E clinical trial (https://castlestudy.org.uk/).